2019
DOI: 10.1002/ijc.32150
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal hormone use and cutaneous melanoma risk: A French prospective cohort study

Abstract: Cutaneous melanoma has been suspected to be influenced by female hormones. Several studies reported a positive association between menopausal hormone therapy (MHT) use and melanoma risk; however, previous findings were conflicting. We sought to explore the associations between MHT use and melanoma risk in a prospective cohort of women in France, where a particularly wide variety of MHT formulations are available. E3N is a prospective cohort of 98,995 French women aged 40–65 years in 1990. MHT use was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 50 publications
10
36
1
Order By: Relevance
“…We found positive associations with unopposed estradiol and unopposed estrogens administrated by cream. This is consistent with the results from the analyses of national data in France, Norway and Sweden, showing a positive association with unopposed estrogens overall (mainly estradiol) . In contrast, previous U.S. studies reported no association with unopposed estrogens, but it should be noted that the main type of estrogens prescribed in the United States is conjugated equine estrogens (CEE), while the main type prescribed in European countries is estradiol, as reflected from the distribution in our population (except for Germany and the United Kingdom for which about half of opposed estrogens were CEE).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found positive associations with unopposed estradiol and unopposed estrogens administrated by cream. This is consistent with the results from the analyses of national data in France, Norway and Sweden, showing a positive association with unopposed estrogens overall (mainly estradiol) . In contrast, previous U.S. studies reported no association with unopposed estrogens, but it should be noted that the main type of estrogens prescribed in the United States is conjugated equine estrogens (CEE), while the main type prescribed in European countries is estradiol, as reflected from the distribution in our population (except for Germany and the United Kingdom for which about half of opposed estrogens were CEE).…”
Section: Discussionsupporting
confidence: 91%
“…MHTs containing promegestone were also positively associated with melanoma risk in our study, consistent with the findings from the French E3N cohort . In sensitivity analyses, MHTs containing norethindrone acetate also became positively associated with melanoma risk.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The use of OCs and MHT has been associated with a higher risk of several cancers, including in the EPIC cohort (breast (18)(19)(20), cervical (21), and endometrial cancer (22,23), and meningioma (24)), and estrogen-only and combined estrogen-progestin hormonal therapy has been classified as carcinogenic to humans (Group 1) by the International Agency for Research on Cancer (IARC) (15,25). With regards to melanoma, while several studies reported a higher melanoma risk associated with exogenous hormone use (26)(27)(28)(29)(30)(31), findings are inconsistent to date. A meta-analysis concluded to no association between exogenous hormone use and melanoma risk (14); however, previous studies were heterogeneous, and few were based on a prospective design.…”
Section: Introductionmentioning
confidence: 96%